The mechanism of action of phenylalanine ammonia-lyase: the role of prosthetic dehydroalanine. - Schuster, B (1995)
Phenylalanine ammonia-lyase (EC 4.3.1.5) from parsley is posttranslationally modified by dehydrating its Ser-202 to the catalytically essential dehydroalanine prosthetic group. The codon of Ser-202 was changed to those of alanine and threonine by site-directed mutagenesis. These mutants and the recombinant wild-type enzyme, after treatment with sodium borohydride, were virtually inactive with L-phenylalanine as substrate but catalyzed the deamination of L-4-nitrophenylalanine, which is also a substrate for the wild-type enzyme. Although the mutants reacted about 20 times slower with L-4-nitrophenylalanine than the wild-type enzyme, their Vmax for L-4-nitrophenylalanine was two orders of magnitude higher than for L-phenylalanine. In contrast to L-tyrosine, which was a poor substrate, DL-3-hydroxyphenylalanine (DL-m-tyrosine) was converted by phenylalanine ammonia-lyase at a rate comparable to that of L-phenylalanine. These results suggest a mechanism in which the crucial step is an electrophilic attack of the prosthetic group at position 2 or 6 of the phenyl group. In the resulting carbenium ion, the beta-HSi atom is activated in a similar way as it is in the nitro analogue. Subsequent elimination of ammonia, concomitant with restoration of both the aromatic ring and the prosthetic group, completes the catalytic cycle.